(untitled) (Revista Apotheke, 2024)
This article presents a study and report on micropractice in teacher training carried out in the municipality of Macapá, as part of doctoral research linked to Estudio de Pintura Apotheke Micropractice was designed based on the conception of investigative teaching based on the concept of knowledge and experience according to John Dewey (1906, 1916, 1928 and 1929) and Josef Albers (1928, 1934, 1935 and 1936). According to John Dewey, the conception of knowledge would be a network of meanings accessible to experience through the association between old and new experiences, thanks to its continuous and retrospective nature. While Josef Albers pointed out ways of practice and experiential teaching in establishing favorable situations for learning from experience. The result of the proposal showed that approaching the principles of selected writings by John Dewey and Josef Albers offer paths for investigative teaching. Just as research combined with the continuous practical experiential process is a possibility of the teacher training path through the training actions offered by Estudio de Pintura Apotheke